Pengembangan Panduan Praktikum IPA Untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Program Studi PGMI Fakultas Tarbiyah dan Tadris IAIN Bengkulu - Sugiarti Sugiarti; Irwan Koto; Daimun Hambali (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
This research aims to develop practical and practical guidelines for basic science concepts to improve critical thinking skills of students of the PGMI Faculty of Tarbiyah and Tadris IAIN Bengkulu who are valid and practical. The research subjects of R & D were 15 students, 7 lecturers and researchers themselves, while the object of this research was a practical guide for basic science concepts courses. This study uses a development model with 4-D procedures recommended by Thiagarajan (1974). In the 4-D development model, there are 4 steps taken to produce a learning development product. The stages include define, design, develop, and disseminate. However, the development of a practical guide for basic science concepts was carried out until the development stage. The instruments used were questionnaires and interview guides for needs analysis, expert validation sheets, legibility test sheets and practicality test sheets. The results showed that the practical guidelines for the basic concepts of science developed were valid, practical and suitable to be used to improve students' critical thinking skills.